A model for promoting poultry industry development in Togo: feeding improvement, capacity building and extension. Issue 3 (29th August 2014) - TONA, K.; KAMERS, B.; TETEH, A.; AGBONON, A.; EKLU-GADEGBEKU, K.; SIMONS, P.; BUYSE, J.; JANSSEN, G.; EVERAERT, N.; KEMP, B.; DECUYPERE, E.; GBEASSOR, M.
<x content-type="archive" xml:space="preserve">Abstract</x> Although being the main bottlenecks for commercial poultry development in Togo, feeding and management practices retain little attention. Indeed, there is no proficient feed miller unit which can provide high quality feed according to the needs of the farmers. This is due to a lack of information on nutrition and relevant management tools or people trained as poultry farm managers. With the aim to alleviate poverty and hunger in Togo, an inter-university project [Catholic University of Leuven (KUL) and University of Lome (UL)] as a model for poultry development was being run from June 2006 to May 2012. Specific objectives of the project are 1) to provide insights and disseminate guidelines and information on adapted methods to improve poultry production and 2) to focus on development of new technologies in poultry production and implementation of research on better poultry nutrition, feeding and management practices.